Wolf and dog depredation on livestock in central Italy - CIUCCI, Paolo; BOITANI, Luigi (WILDLIFE SOC, 1998)
We investigated wolf (Canis lupus)- and dog-livestock conflicts (1992-1995) and costs of compensation (1991-1995) in the Tuscany region of central Italy. The regional indemnity program cost US $345,000 (+/- 93,000 SD) annually. Most depredations (95.2%) involved sheep, with a mean (+/- SD) annual loss of 2,550 +/- 730 sheep, or 0.35% of the regional stock. Sheep lost to predators by province were correlated with sheep density within areas containing wolves (r(s) = 0.88, n = 9, P = 0.0015), but marked geographical and temporal fluctuations were reported in compensation costs. Highest levels of conflict were observed in the provinces at the border of the regional wolf range, where livestock was left unattended most of the year and sheep density reached its highest regional levels. Based on 527 reports of approved claims during 1992-1995 from the National Health System, depredations were highly seasonal, increasing steadily from spring to early fall, possibly following trends in sheep availability on pastures and density fluctuations of local wolf packs. An average of 3 sheep (range = 1-18)were killed per attack (n = 483), and 42% of the attacks involved killing of less than or equal to 2 sheep. Additionally, 21-113 sheep were killed or attacked in mass slaughters which comprised 2.3% of the depredation events and 19% of the sheep lost. Depredations also resulted in 35% (n = 168) of sheep injured and 33% (n = 158) missing. Most sheep depredations occurred during the night, in pastures interspersed with wood or vegetative cover, and involved free-ranging flocks unattended by either the shepherd or guard dogs. High levels of conflict occurred in localized areas of intensive sheep production; 6% of the affected farms and 8% of the affected municipalities accounted for 32% of the sheep lost to both wolves and dogs at the regional level. Compensation programs alone were not effective in reducing the conflict or in preventing illegal, private efforts to control wolf numbers. Improved husbandry should be encouraged and ...